Silent privatisation of customary land in Zambia: opportunities for a few, challenges for many - Chitonge, Horman; Mfune, Orleans; Umar, Bridget B.; Kajoba, Gear M.; Banda, Diana; Ntsebeza, Lungisile (Social dynamics, 2017)
The conversion of customary land into leasehold tenure has sparked intense debates in Zambia and beyond. Growing interest in land in the last decade and half has led to a spike in demand for land across Africa, especially land adjacent to major cities, towns and developed infrastructure. This growing demand for land is gradually being directed at customary land, which well-resourced urban and local elites, as well as foreign investors, are converting from customary to private tenure, raising serious questions about the future of customary land in Africa. This paper discusses the emerging dynamics around customary land conversion drawing from a case study conducted in Chongwe and Chibombo districts in Zambia. Evidence gathered in this study suggest that while the conversion of customary land to leasehold tenure is generating opportunities for the urban elite, a few traditional leaders and international investors, it is, at the same time, creating serious challenges for the majority of the people in the local communities.